Evolution of Surface Acoustic Waves in an Optical Microfiber - Emami S.D.; Jing L.H.; Rahman M.M.; Abdullah F.; Abdul-Rashid H.A.; Dashtabi M.M.; Azizur Rahman B.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Acoustic surface wave devices; Acoustic waves; Antimony; Finite element method; Numerical methods; Optical fibers; Stimulated Brillouin scattering; Core-cladding interfaces; Displacement vectors; Fiber cores; Micro-fiber; Surface acoustic waves; Tapered optical fibers; Wave numbers; Acoustic wave propagation